Clasicismo frente a modernidad, el arte frente a la técnica: estructura y significado de los viajes en Homo faber de Max Frisco - Hernández, Isabel (Revista de Filología Románica, 2006)
The journey as a literary motive occupies a central position in Max Frisch’s novel Homo Faber (1957) which has barely been granted attention by the field of literary studies, which has been more interested in analyzing other themes or motives present in the novel, such as incest, the modern man or the Oedipus’ complex. However the journey is precisely the structure which gives shape to Frisch’s novel. Afirst journey to the new world (Central America) which is followed by another to Old Europe, both described from the perspective of the Americanized European living in the land of technology and possibilities: the United States of America. The images of the two continents conveyed to the reader through the eyes of this infatigable traveler is a personal, subjective version, which confronts both worlds with two different mentalities. This conflict culminates in a final situation completely unexpected by the main character: the confrontation with himself. The objective of the literary journey goes in this case beyond the mere description of situations, landscapes or people to portray the search for one’s own identity.